Grain size matters: Implications for element and isotopic mobility in titanite - Kirkland, C.; Spaggiari, C.; Johnson, T.; Smithies, R.; Danišík, Martin; Evans, Noreen; Wingate, M.; Clark, C.; Spencer, C.; Mikucki, E.; McDonald, B. (Elsevier BV, 2016)
The U–Pb isotopic signature of titanite collected across an exhumed refractory lower crustal block within the Albany–Fraser Orogen, Australia, records thermal overprints not apparent in a suite of other U–Pb chronometers. This helps to reconcile a dichotomy within the geochronological record of two adjacent zones within the orogen. The zircon U–Pb record for the older Biranup Zone preserves widespread overprinting at 1225–1140 Ma (Stage II), whereas the younger Fraser Zone records an older 1330–1260 Ma (Stage I) tectonothermal event. Titanite in the Fraser Zone also predominantly records a U–Pb age of 1299 ± 14 Ma, reflecting the interval of closure to radiogenic Pb mobility. Nonetheless, small titanite grains reveal subsequent overprinting with a mean reset age of 1205 ± 16 Ma. By contrast, titanite from metasedimentary rocks within the adjacent Biranup Zone principally record U–Pb ages of 1200–1150 Ma, interpreted as dating cooling after prolonged Stage II metamorphism. Interestingly, titanite also preserves domains with old apparent ages.These domains have a statistically significant association with lower U content and also indicate reduced Sm/Yb ratios and are interpreted to have lost U but acquired HREE (e.g. Yb) more rapidly than MREE (e.g. Sm). The old apparent ages are interpreted as artefacts of a Stage II U redistribution process, leading to unsupported radiogenic Pb. In addition, titanite grain size has a strong effect on the preservation or resetting of metamorphic U–Pb ages. Thermochronological modelling based on apparent age versus grain size relationships indicates that complete resetting of small titanite grains requires overprinting temperatures of 695–725 °C during Stage II in the Fraser Zone. This result is similar to estimates from the Biranup Zone based on phase equilibrium modelling that indicates pressures and temperatures of 6.5–8.5 kbar and 675–725 °C. An in situ U–Pb analysis strategy for titanite that targets a range of grain sizes has the potential to reveal differential resetting and place important controls on thermal history.